Certifying Credibility: Trajectory of Sub-Saharan Asylum Seekers in Italy - Oubad, Ismail; Mouna, Khalid (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
"A ‘truthful’ protection seeker would initiate their story with “because” or “because of”, underlining the necessity and the urgency of their displacement, which may be linked to war, genocide, natural disaster… Unlike the so-called ‘truthful’ protection seeker, the use of “for” and “so” turns the subject into a suspect, leaving his country to improve his living conditions, live a new adventure and pursue self-realization, something not allowed to people from the Global South. Drawing on an ethnography with refugees and protection seekers in Italy (region of Veneto), testimonies were generated to look at the complex processes involved in certifying eligibility to legal protection. This paper underscores the conditions under which migrants (re)invent a new identity to meet the institutional expectations of the European humanitarian criteria for asylum-seekers."